Cooperative Language Learning Method In Teaching Vocabulary And Word Expression To Junior High School Students - Faisal, Faisal; Anggraini, Anggraini; Wibowo, Ary Iswanto (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the implementation of Cooperative Language Learning (CLL) in teaching vocabulary and word expressions to junior high school students at SMP Buddhi Tangerang. The need for fundamental English learning, particularly in vocabulary mastery, was identified during classroom observations, where many students demonstrated limited ability to understand and use basic English expressions. The teaching process involved introducing familiar expressions and assessing students’ vocabulary through interactive activities such as games and song analysis. The CLL method was implemented collaboratively, emphasizing group discussions, peer interaction, and shared responsibility to enhance learning effectiveness and student engagement. This approach also encouraged students to actively participate and express their ideas in a supportive learning environment. The findings reveal a significant improvement in students’ performance, as indicated by higher scores in the final assessment compared to the initial assessment, based on predetermined evaluation criteria. In addition, students demonstrated increased confidence and participation during classroom activities. Therefore, the implementation of CLL is considered effective in improving vocabulary mastery and word expression among junior high school students.